Too little or too Much Freedom? – A Comparative Analysis of Corporate Governance Codes in the UK and Australia - Alanazi, Badar (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
The purpose of corporate governance codes is to ensure that directors do not abuse their power to the disadvantage of the company’s shareholders or creditors, while at the same time affording them enough freedom to allow the company to operate in a competitive way and generate profits. This article evaluates the UK Corporate Governance Code and the Australian Corporate Governance Principles and Recommendations in order to ascertain the extent to which they strike an appropriate balance between preventing abuses of power by the board while affording them sufficient freedom to pursue innovation and entrepreneurship. The article concludes that the codes in both countries propose advanced approaches to corporate governance which to a significant extent protect the interests of the shareholders while encouraging board members to pursue innovation and entrepreneurship in a safe manner, through the adoption of appropriate risk management measures.